Comportamento super-Arrhenius na difusão do criptônio em metanol : uma análise via dinâmica molecular de Car-Parrinello - (:unkn) unknown (Universidade Estadual de Goiás, 2016)
This dissertation presents a study of the diffusion properties of krypton in methanol. At temperatures above the melting temperature, the Kr in methanol exhibits behavior in accordance with the Arrhenius law, however, at low temperatures methanol acquires a behavior which is not in accordance with the prediction of the Arrhenius law, which is called super-Arrhenius. For a better understanding of krypton in methanol diffusion properties and to make a comparison with the experimental results, molecular dynamics Car-Parrinello was used to perform simulations in the glass transition temperature. Four simulations were completed at temperatures of 85K, 90K, 95K and 100K using the PBE functional and Vanderbilt ultrasoft pseudopotential. The calculations were performed for the mean square displacement, radial distribution function, the comparison between the experimental and molecular dynamics results was performed by comparing the Arrhenius diagram experimental data with both molecular dynamics results and fitting obtained by the d-Arrhenius approach. In addition to the procedures mentioned above were also made DFT and e Coupled cluster calculations for a better understanding of the interaction between krypton and Oxygen methanol, from the energy point of view. The results reaffirm the non-Arrhenius behavior for the diffusivity of methanol and indicate that not happen spontaneous interactions between krypton and methanol molecules.
Keywords: Dinâmica molecular; Car-Parrinello; Lei de Arrhenius; uper-Arrhenius; Super-Arrhenius; Molecular dynamics; Car-Parrinello; CIENCIAS EXATAS E DA TERRA::QUIMICA; QUIMICA::FISICO-QUIMICA